2012
DOI: 10.1063/1.4757964
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electron magnetic resonance spectra of iron oxide nanoparticles mineralized in Listeria innocua protein cages

Abstract: Electron magnetic resonance (EMR) spectroscopy was used to determine the magnetic properties of maghemite (c-Fe 2 O 3 ) nanoparticles formed within size-constraining Listeria innocua (LDps)-(DNA-binding protein from starved cells) protein cages that have an inner diameter of 5 nm. Variable-temperature X-band EMR spectra exhibited broad asymmetric resonances with a superimposed narrow peak at a gyromagnetic factor of g % 2. The resonance structure, which depends on both superparamagnetic fluctuations and inhomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Similar symmetrical narrow line with g≈2 was observed by several authors for different nanoparticle ensembles [4,22,23,24]. According to Ref.…”
Section: Emrsupporting
confidence: 67%
“…Similar symmetrical narrow line with g≈2 was observed by several authors for different nanoparticle ensembles [4,22,23,24]. According to Ref.…”
Section: Emrsupporting
confidence: 67%
“…Two distinct resonances (broad and narrow) were attributed to a core-shell structure from the analysis of their temperature dependent linewidths. [35][36][37] The narrow line was assigned to surface spins or very small particles. Noginova et al found that the narrow line of a γ-Fe 2 O 3 (d = 4.8 nm) ferrofluid gradually broadened upon increase of the concentration.…”
Section: Ferromagnetic Resonance (Fmr) Propertiesmentioning
confidence: 99%
“…FMR is also an informative technique to investigate the internal spin dynamics responsible for the relaxation processes in ferromagnetic nanoparticle systems. [8][9][10][11][12][13][14][15] Here, we describe the FMR studies of MgO:Ni to gain a physical insight into magnetic interactions and local anisotropy field phenomena.…”
Section: Introductionmentioning
confidence: 99%